Near-surface topology and flow structure on a delta wing with low sweep angle - Elkhoury, Michel (2017)
The patterns of streamline topology, surface-normal vorticity and fluctuating velocity are characterized immediately adjacent to the surface of a delta wing having a low sweep angle (Λ=38º) using a cinema technique of high-image-density particle image velocimetry. The critical points of the topological structure, including foci, nodes and bifurcation lines, are determined in relation to patterns of vorticity and velocity and, in turn, compared with dye visualization, as well as time-averaged approximations to the topology obtained using oil film visualization in a previous wind tunnel experiment. It is demonstrated that the classical time-averaged topology is actually attributable to a series of quite different instantaneous topological states. Small-amplitude perturbation of the angle-of-attack of the wing at an appropriate frequency is shown to radically alter the time-averaged topology, as well as the patterns of velocity fluctuation associated with buffet loading of the wing.